Physics engine-driven visualization of deactivated elements and its application in bridge collapse simulation - Xu, Zhen; Lu, Xinzheng; Guan, Hong; Ren, Aizhu (Automation in construction, 2013)
Element deactivation is one of the most suitable methods in a finite element (FE) analysis of discontinuous features of collapse accidents. However, deactivated elements are typically invisible in the general purpose FE analysis, leading to a very incomplete outcome. To visualize the deactivated elements, a 3D simulation method of fragments based on a physics engine is proposed herein. A working system for fragment simulation is designed by integrating a graphics engine, an FE analysis and a physics engine. To reduce the extensive computational workload due to massive fragments, a grid-clustering algorithm for fragment modeling is also proposed. Using the proposed simulation methodology, the collapse processes of two bridges are completely replicated. The results demonstrate a realistic and real-time visual simulation of deactivated elements, which complements the limitations of the general FE analysis results. This study provides an important reference for conducting detailed investigations of bridge collapse accidents. A 3D real-time visualization method of deactivated elements using fragment simulation is proposed to reconstruct a complete process of bridge collapses, which complements the limitations of the general FE analysis results. [Display omitted] •We propose a visualization method of deactivated elements by fragment simulation.•We reconstruct a complete process of bridge collapses in a 3D visual simulation.•Visual simulation of bridge collapse is real-time.•Fragment simulation has proven accurate.•Fragment simulation complements the limitations of the general FE analysis results.